Comparison of P1 and 16S rRNA genes for detection of Mycoplasma pneumoniae by nested PCR in adults in Zhejiang, China - Zibo Zhou; Xiangzhi Li; Xiaojian Chen; Lili Yao; Changwang Pan; Huicong Huang; Fangjun Luo; Xiaoping Zheng; Xiaojing Sun; Feng Tan (Journal of Infection in Developing Countries)
Introduction: Mycoplasma pneumoniae (M. pneumoniae) is the most common atypical pathogen that causes respiratory infections in humans. Laboratory tests are important in the diagnosis of M. pneumoniae because of the atypical features in clinical signs and symptoms. Nowadays, both the P1 adhesin gene and 16S ribosomal (r) RNA (rRNA) gene of M. pneumoniae have been widely detected by polymerase chain reaction (PCR). The purpose of the present study was to evaluate the most suitable target in the detection of M. pneumonia via nested PCR. Methodology: Both the P1 adhesin gene and 16S rRNA gene for nested PCR reaction conditions were optimized through an orthogonal test and single-factor experiment. Then, the sensitivity of the two sets of targets was evaluated. Finally, based on the optimal conditions, 55 clinical samples of throat swabs collected from adult patients in 2013 were examined by established nested PCR. Result: The results revealed that PCR detection of the 16S rRNA gene was more sensitive than the P1 adhesin gene because the detection limits for both the P1 gene and 16S rRNA gene were at least 100 fg and 10 fg of M. pneumoniae DNA, respectively. Furthermore, the positive rate for detection of the 16S rRNA gene (30/55; 54.5%) was higher than that of the P1 adhesin gene (25/55; 45.5%). Conclusion: Our results indicate that the 16S rRNA gene is more suitable for diagnosis of M. pneumoniae infection than the P1 adhesin gene due to its higher sensitivity and positive rate in clinical samples.